Cross-cultural validation of the sport emotion questionnaire using elite hockey players: psychometric evidence from seven African countries - Quansah, F.; Srem-Sai, M.; Agormedah, E. K.; Quansah, N.; Tannoubi, A.; Hagan Jr., J. E.; Schack, T. (International Journal of Sport and Exercise Psychology, 2026)
The Sport Emotion Questionnaire (SEQ) is a popular measure of the emotions of athletes prior to a competition. Although several validation studies have assessed the SEQ`s psychometric properties, the findings have been inconsistent. The study examined the (a) structure of the SEQ, (b) variance contribution and discriminant analyses of the SEQ, and (c) reliability of the instrument across different groups of sports performers from seven African countries. A diverse convenient sample of sports performers (n = 423) completed the SEQ before competition. Using the confirmatory factor analysis across all countries, the five-factor first-order model best fits the data compared with the other proposed competing models. Further, the AVE values together with the loadings showed an adequate level of convergent and discriminant validity (based on internal structure), with all the average variance extracted (AVE) and heterotrait-monotrait (HTMT) values larger than 0.50 and less than 0.90, respectively. Additionally, the reliability coefficients of the sub-dimensions of the SEQ were greater than 0.70. Generally, the observed evidence supports the validity and reliability of the SEQ as a measure of expressed emotions by sports performers in a sports environment during competitions. Recommendations and conclusions are drawn from the findings.